Prevalence and genetic characterization of Cryptosporidium spp. and Cystoisospora belli in HIV-infected patients - Assis, Dnieber Chagas; Resende, Deisy Vivian; Cabrine-Santos, Marlene; Correia, Dalmo; Oliveira-Silva, Márcia Benedita (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
Cryptosporidium spp. and Cystoisospora belli are monoxenic protozoa that have been recognized as the causative agents of chronic diarrhea in immunocompromised individuals, especially HIV-infected subjects. The objective of this study was to evaluate the frequency of these intestinal protozoa in HIV-positive patients in the Triângulo Mineiro region of Brazil and to correlate the presence of these infections with clinical, epidemiological and laboratory data of the patients. Oocysts were detected in stool samples of 10 (16.9%) of the 59 patients studied, while Cryptosporidium spp. were present in 10.1% (6/59) and C. belli in 6.7% (4/59). The frequency of these parasites was higher among patients with diarrheic syndrome and CD4+ T lymphocyte counts < 200 cells/mm 3 , demonstrating the opportunistic characteristic of these infections. A significant association was observed between the lack of adherence to antiretroviral therapy and the presence of Cryptosporidium spp. and/or C. belli. Parasitism with Cryptosporidium spp. was more frequent in February and April, the months following the period of high rainfall. The same was not observed for C. belli. Genetic characterization of two isolates led to the identification of Cryptosporidium parvum, one of the main species associated with the zoonotic transmission of cryptosporidiosis.